Prevalence of elevated aldosterone renin ratio in three main states of Peninsular Malaysia - Saud Gany, Siti Liyana; Shahar, Mohammad Arif; Sukor, Norlela; Omar, Ahmad Marzuki; A Wahab, Norasyikin; MY, Yusniza; Azizan, Elena; Chong, Kuck Meng; Md Zain, Rabizah; Long, Kha Ching; Mohd Razali, Amyliation; Zainuddin, Noradilah; et al. (Malaysian Endocrine & Metabolic Society (MEMS), 2016)
Objective: The objective of this study was to determine the prevalence of increased Aldosterone Renin Ratio (ARR) in parts of Selangor, Perak and Pahang.